On The Gibbs Phenomenon for \(|N,p_n,q_n|\)-Summability Method - Raghuvanshi, Aditya Kumar (Communications in Mathematics and Applications, 2014)
In this paper we have proved a theorem on the Gibbs phenomenon for \(|N,p_n,q_n|\)-summability method which gives some new results and generalizes some previous known results.